PHYSICAL AND GERMINATIVE CHARACTERISTICS OF Trichilia claussenii C.DC. FOR THE REGION OF THE HIGH MEDIUM URUGUAY – RS - Maffra, C. R. B. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The knowledge of the germinative aspects of native species of the Deciduous Forest is important to promote recovery programs in forest fragments in this phytoecological region. In this sense, the present study aimed to determine the physical and germinative aspects of seeds of Trichilia claussenii C.DC. For the determination of the weight of one thousand seeds, eight repetitions of 100 seeds each were used and the coefficient of variation was calculated. For the moisture content, 4 repetition of 25 seeds were used, which were dried in an oven at 105 ºC ± 3°C for 24 hours. Sixteen replicates of 25 seeds were placed in gerbox plastic boxes with vermiculite, moistened with distilled water and placed in a germination chamber (BOD), to determine the rate of germination velocity (GV) and final germination (FG). The weight of one thousand seeds was 851 g (1,175 seeds/kg and CV=1.7%) with humidity of 39.2%. The GV found was 2.8 and the final germination was 73.3%. This information is useful for the species’ silviculture.